Are mobile phones safe?. - Foster, K.R.
Driven in part by disturbing allegations, a new wave of research in the United States and elsewhere is exploring possible links between cell phone radiation and cancer. Brain cancer, the topic of this article, is not the only health concern, but it dominates public discussion. A substantial body now exists of pertinent scientific evidence. This article discusses EM fields and research on looking for a link between them and cancer. The results of animal studies are briefly outlined. The article discusses exposure limits to RF radiation
Keywords: EM fields; RF radiation exposure limits; United States; Animal studies; Brain cancer; Cell phone radiation; Health concern; Mobile phones; Research; Scientific evidence